ALTER ACCOUNTS AS SAFE SPACES IN GENERATION Z PRIVACY MANAGEMENT ON INSTAGRAM - Mika Lorensia Ginting; Roziana Febrianita (INJOSEDU: International Journal of Social and Education, 2026)
Social media's rapid growth has transformed how Generation Z builds relationships, constructs identities, and manages privacy online. On Instagram, the use of both main and alter accounts reflects a shift in privacy management, where users regulate access to personal information through interaction restriction features based on audience, context, and perceived risk. Despite widespread use of these practices, little research has examined how such features shape Generation Z's privacy management. This study therefore examines how Generation Z manages privacy through Instagram's interaction restriction features on main and alter accounts, using a descriptive qualitative approach within a constructivist paradigm. Data were collected through in-depth interviews, observation, and documentation involving ten Generation Z participants aged 18–25 who actively use both account types and have experience with these features. Data were analyzed using Communication Privacy Management (CPM) theory, focusing on privacy boundaries, privacy rules, and boundary turbulence. Findings show that privacy management is dynamic, layered, and relational: boundaries are formed by separating main and alter account functions and using features like Private Account, Close Friends, Hide Story, Mute, and Block; rules are shaped by relational closeness, gender, context, and risk perception; and turbulence arises when private information reaches unintended audiences or restrictions strain relationships.